THE INFLUENCE OF SERVICE QUALITY ON BRAND IMAGE IN THE COMMUNITY(Case Study at Bank Bjb Sukajadi Branch) - Rama Tresnadi; Sri Rochani Mulyani; Zaenal Aripin (Organisasi Kreatif Indonesia Emas, 2024)
This study aims to assess the extent of the influence of Service Quality (SerQual) on brand image at PT Bank Bjb Sukajadi Branch. This research has important relevance given the intense competition among banks and non-bank financial institutions. By taking a sample of customers who were borrowers and depositors during the period 2019 to 2021, 100 respondents were involved in this study. The research method used is a quantitative approach with multiple regression analysis. The results of the regression model show a positive coefficient, indicating that any change in service quality has the potential to affect brand image. The coefficient of determination (R2) is 72.8%, indicating that service quality has a significant influence on brand image. The results of hypothesis testing, both partially and simultaneously, show a positive and significant effect of service quality on brand image. The implications of this study show that physical evidence contributes significantly to brand image, while responsiveness contributes less. These results provide a better understanding of the elements of service quality that need to be considered to improve brand image in the banking industry.